The Influence of Investments and Government Expenditures to Economic Growth and Employment Opportunities in Kutai Kartanegara District - Ariani, Rita; Amalia, Siti; Hudayah, Syarifah (Green Publisher, 2022)
The goal to be achieved through this research is to analyze the variables that affect government investment and expenditure on economic growth and employment opportunities in Kutai Kartanegara Regency, using the Path Analysis method. This is a causality study, which analyzes the effect of exogenous variables on endogenous variables. The variables used are investment variables, government spending, economic growth and employment opportunities in Kutai Kartanegara Regency. The data used in this study are secondary time series data from 2010 to 2020 sourced from BPS and the Ministry of Finance. The data that has been collected is then analyzed quantitatively and qualitatively to provide the proposed hypothesis using Path Analysis. The results show that simultaneous research shows that Investment and Government Expenditure have a significant effect on economic growth. Partially, investment has a positive and significant effect on economic growth, government spending has a negative and insignificant effect on economic growth. Investment has a positive and significant effect on Employment Opportunities. Government spending has a negative and insignificant effect on employment opportunities.